Submicroscopic deletions and duplications in individuals with intellectual disability detected by array-CGH - Tyson, C.; Harvard, C.; Locker, R.; Friedman, J.M.; Langlois, S.; Lewis, M.E.S.; Van Allen, M.; Somerville, M.; Arbour, L.; Clarke, L.; McGilivray, B.; Yong, S.L.; et al. (American journal of medical genetics. Part A, 2005)
Intellectual disability (ID) affects about 3% of the population (IQ < 70), and in about 40% of moderate (IQ 35–49) to severe ID (IQ < 34), and 70% of cases of mild ID (IQ 50–70), the etiology of the disease remains unknown. It has long been suspected that chromosomal gains and losses undetectable by routine cytogenetic analysis (i.e., less than 5–10 Mb in size) are implicated in ID of unknown etiology. Array CGH has recently been used to perform a genome‐wide screen for submicroscopic gains and losses in individuals with a normal karyotype but with features suggestive of a chromosome abnormality. In two recent studies, the technique has demonstrated a ∼15% detection rate for de novo copy number changes of individual clones or groups of clones. Here, we describe a study of 22 individuals with mild to moderate ID and nonsyndromic pattern of dysmorphic features suspicious of an underlying chromosome abnormality, using the 3 Mb and 1 Mb commercial arrays (Spectral Genomics). Deletions and duplications of 16 clones, previously described to show copy number variability in normal individuals [Iafrate et al., 2004; Lapierre et al., 2004; Schoumans et al., 2004; Vermeesch et al., 2005] were seen in 21/22 subjects and were considered polymorphisms. In addition, three subjects showed submicroscopic deletions and duplications not previously reported as normal variants. Two of these submicroscopic changes were of de novo origin (microdeletions at 7q36.3 and a microduplication at 11q12.3‐13.1) and one was of unknown origin as parental testing of origin could not be performed (microduplication of Xp22.3). The clinical description of the three subjects with submicroscopic chromosomal changes at 7q36.3, 11q12.3‐13.1, Xp22.3 is provided. © 2005 Wiley‐Liss, Inc.